Polydopamine Nanoparticles-Based Photothermal Effect Against Adhesion Formation in a Rat Model of Achilles Tendon Laceration Repair - Zhou Z; Li S; Gong X (International Journal of Nanomedicine, 2023)
Zekun Zhou,1,2 Shaoyan Li,1,2 Xu Gong1,2 1Department of Hand and Podiatric Surgery, Orthopedics Center, The First Hospital of Jilin University, Changchun, 130021, People’s Republic of China; 2Jilin Province Key Laboratory on Tissue Repair, Reconstruction and Regeneration, The First Hospital of Jilin University, Changchun, 130021, People’s Republic of ChinaCorrespondence: Xu Gong, Department of Hand and Podiatric Surgery, Orthopedics Center, The First Hospital of Jilin University, Changchun, 130021, People’s Republic of China, Tel +86 13944099151, Email gongxu@jlu.edu.cnBackground: Adhesion formation after tendon surgery is a major obstacle to repair of tendon ruptures, and there is still no effective clinical anti-adhesion method. Myofibroblasts expressing α-smooth muscle actin (α-SMA) play a crucial role in adhered fibrous tissue. Heat shock protein (Hsp) 72 can selectively prevent the activation of c-Jun N-terminal kinase (JNK), which mediates the conversion from fibroblasts to myofibroblasts. The purpose of this study was to investigate for the first time whether polydopamine nanoparticles (PDA NPs)-based photothermal effect would attenuate adhesion formation in a rat model of Achilles tendon laceration repair.Materials and Methods: Forty-five adult male Sprague-Dawley rats were randomly assigned to the photothermal group, the control group and the PDA NPs group (n = 15 per group). The primary outcome measure was the adhesion scores at two weeks after surgery according to the grading of Tang et al. The secondary outcomes included the expressions of Hsp 72, JNK, phosphorylated JNK and α-SMA, which were measured by immunohistochemistry or Western blot.Results: The average adhesion score was significantly lower in the photothermal group (4.25 ± 0.21) than that in the control group (5.29 ± 0.12) (p = 0.005) and the PDA NPs group (5.29 ± 0.20) (p = 0.005). Relative to the control group and PDA NPs group, Hsp 72 in the photothermal group was significantly increased whereas α-SMA and p-JNK was significantly decreased, but JNK was not found to be different across the three groups.Conclusion: The photothermal effect produced by PDA NPs could reduce tendon adhesion formation in rats by inhibiting myocyte fibrosis, which may have potential in developing endogenous heating for postsurgical tissue adhesions.Keywords: adhesion formation, tendon, polydopamine nanoparticle, photothermal effects